Implementasi Etnomatematika Dalam Permainan Materi Geometri Di Sekolah Dasar - Nur Aini, Fathiya; Dia Indah Sari, Arissona (ALENA : Journal of Elementary Education, 2024)
Traditional games are a type of culture that is often found in Indonesia. With the development of technology, elementary school students are now highly exposed to electronic devices. As a result, many young people today do not know traditional games. Children will most likely forget traditional regional games if they are not introduced to them. The aim of this research is to introduce traditional games to today's elementary school students by combining learning, especially mathematics, with traditional games. In this research, the traditional game used was the engklek game. This research approach uses written sources such as articles, journals and documents that are relevant to the research focus. The research method applied is a literature review method with a qualitative approach. The research results show that the use of traditional games such as engklek can increase students' interest in learning mathematics and also improve their learning outcomes significantly. Further research that would be interesting to develop could be related to learning mathematics through other traditional games related to the concept of geometry or measurement.